NEGARA DAN KEBIJAKAN DISKRIMINASI: POLA KEBIJAKAN NEGARA DALAM MENGAKOMODIR AGAMA-AGAMA LOKAL DI INDONESIA - Zaenuddin Zaenuddin (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This article aims to analyse and describe how the policy made by the state in terms of local religions, especially in the context of civil rights services such as administration document management. By using the library research method, this article aims to explore various problems  that arise when local religion confront and deal with the state in the service of civil rights. The basis of the recognition lies in the defining and purposing of religions adopted by the state. Religion is defined as something that has the Scriptures (based on written scripture), the Prophet or Apostle, the divine doctrine of the almighty and gaining international recognitions. This definition is strongly influenced by the world’s religious paradigms. This definition then places the local religions, not as religious people in the state. So that they are not acommodated  in public services due to religion or belief that they are not official religions recognized by the country. So that the country offers a policy effoerts to uniformity religion through conversion (moving) religion to one of the official religion or local religious beliefers who perform religious syncretism  by following certain religions are only limited legal obligations but do not carry out the following religious duties. The aims is to facilitate them in the fulfillment and service of civil rights